2013
DOI: 10.2320/matertrans.mbw201204
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Stability and Thermoelectric Property of Alkali-Metal-Encapsulated Type-I Silicon-Clathrate from First-Principles Calculation

Abstract: Possible combinations of alkali metal guest atoms and substitutional group-13 atoms in type-I Si clathrate and their thermoelectric properties were investigated using first-principles calculations. All alkali metals could be encapsulated as the guest element into a Si 46 cage, and either Al or Ga was suitable for a substitutional atom. From the formation energy, possible clathrate compositions were selected as K 8 38 . The thermoelectric properties of these compositions were calculated as functions of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…Changing the carrier concentration by tuning the electronic structure through element substitution could increase the Figure of merit for A 8 Al 8 Si 38 clathrates significantly. Theoretical calculations performed by Nakamura et al for A 8 Tr 8 Tt 38 clathrates showed that the Figure of merit for optimally doped compounds can reach 0.5 already at 600 K, and for hole‐doped Cs 8 Ga 8 Si 38 even a ZT value of 0.75 at 900 K can be achieved 11. Comparably high values were also calculated by Karttunen et al for alkali‐metal E III / E IV clathrate‐II compounds 12…”
Section: Introductionmentioning
confidence: 76%
“…Changing the carrier concentration by tuning the electronic structure through element substitution could increase the Figure of merit for A 8 Al 8 Si 38 clathrates significantly. Theoretical calculations performed by Nakamura et al for A 8 Tr 8 Tt 38 clathrates showed that the Figure of merit for optimally doped compounds can reach 0.5 already at 600 K, and for hole‐doped Cs 8 Ga 8 Si 38 even a ZT value of 0.75 at 900 K can be achieved 11. Comparably high values were also calculated by Karttunen et al for alkali‐metal E III / E IV clathrate‐II compounds 12…”
Section: Introductionmentioning
confidence: 76%
“…26 According to this work the impact of guest atoms on the band gap should be minimal. The effect of the framework cations on the electronic structure is much stronger, 26 which explains the observed narrowing of the band gap (1.40 to 1.18 eV) (see Table 3) upon replacing Al with Ga atoms. Based on the negative sign of the photovoltage, all compounds behave as n-type semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…E and K are Young's and bulk moduli, respectively. The average bond distance refers to structures at room temperature with the mentioned space-groups.An interesting similarity to HaPs in sense of their crystal structure (cubic) and surprisingly low thermal conductivity30,31 , can be found in a structural family called clathrates. Inorganic clathrate compounds (e.g., K 8 Al 8 Si 36 , Sr 8 Ga 16 Ge 30 ) are characterized by an open framework structure with 'guest' ions (e.g.…”
mentioning
confidence: 99%